13 No molecular evidence for the role of the genetic background of the host in explaining lymph node metastasis in head and neck cancer. Issue 5 (May 2015) - Mes, S.; Braakhuis, B.J.M.; Bloemena, E.; van Wieringen, W.N.; Leemans, C.R.; Brakenhoff, R.H.
Abstract : Introduction: It has been shown for head and neck squamous cell carcinomas (HNSCC), that a specific gene expression profile in the primary tumor has predictive value for the presence of a lymph node metastasis. It is possible that these expression profiles are a result of acquired cancer-associated genetic aberrations during tumorigenesis. The alternative hypothesis, based on genetic studies in the mouse, is that the variation in the genome of the host determines the risk for metastasis. Aim of this study was to measure the global gene expression of the normal mucosa and the tumor as control of HNSCC patients to establish whether there is a difference between patients with and without lymph node metastasis. In addition, the paired analysis allowed the assessment of differential gene expression of HNSCC versus corresponding normal mucosa. Material and methods: We examined the global gene expression of normal oral mucosa and the paired tumors from 22 HNSCC patients of whom eight patients were with and fourteen without lymph node metastasis. Five HNSCC were in the oropharynx and 17 in the oral cavity; only HPV-negative tumors were selected. Cross-validation was used to establish the predictive value of a gene expression profile. Results: We showed in this case-control comparison that a gene expression profile in tumors had significant predictive value, as previously reported. When using expression profiles of the corresponding normal mucosa, however, the predictive value was lower and can be considered of little or no value for the prediction of lymph node status. Approximately 1600 unique and mapped transcripts were significantly and differentially expressed between tumor and mucosa, based on an p -value <0.05 and a fold-change ⩽0.5 or ⩾2.0. Canonical pathways related to immune cell adhesion and extravasation and extra-cellular matrix remodeling were altered in tumor cells. Conclusions: This study provides evidence that the metastatic potential in HNSCC is likely the result of the cancer-associated genetic changes, and not related to the genetic variation in the host. Second, we obtained a comprehensive and valuable view on the gene expression difference between HNSCC and paired normal mucosal tissue.